Effect of cultivars, populations and localities on seed quality of soybeans - Maeda, Jocely Andreuccetti; Mascarenhas, Hipólito A.A.; Almeida, Luiz D’Artagnan de; Nagai, Violeta (Pesquisa Agropecuaria Brasileira, 2014)
Experiments were installed at four localities in soils of low fertility of "cerrado" recently recuperated, to explore the possibility to produce seed of good quality. Three cultivars (Santa Rosa, IAC-1 and IAC-2) and three populations (250.000, 333,000 and 500,000 plants per hectare) were utilized for this purpose. During the storage period laboratory tests were made every two months to evaluate on the germination. The vigor, the weight of 100 seeds, and its moisture content were also measured. Analysing each parameter separately, IAC-1 weighed more than Santa Rosa, and IAC.2 whereas the latter two showed greater germination and vigor. Among populations under study 250.000 plants per hectare was the best treatment for seed weight and there was very little difference among population for germination and vigor of seed. Among localities, the weight of seeds was similar at São Simão, Bento Quirino and Mococa whereas at Aguaí the seed quality was better.